2005
DOI: 10.1093/jn/135.6.1400
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Dietary Habits Affect Soy Isoflavone Metabolism and Accumulation in Prostatic Fluid in Caucasian Men

Abstract: The soy isoflavones daidzein and genistein are believed to reduce prostate cancer risk in soy consumers. However, daidzein can be metabolized by the intestinal flora to form a variety of compounds with different bioactivities. In the current study, we investigated the influence of long-term dietary habits on daidzein metabolism in healthy Caucasian men (19-65 y old). A secondary goal was to compare plasma and prostatic fluid concentrations of 5 isoflavonoids: genistein, daidzein, equol, dihydrodaidzein, and O-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
86
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 36 publications
4
86
0
Order By: Relevance
“…Previous laboratories, including ours, have shown that isoflavones binding to ER-β in the prostate can down regulate the AR and thus decrease negative androgen hormone actions [28]. Moreover, this may explain how isoflavonoid molecules accumulate in prostate tissue and prostatic fluid after oral supplementation [29,30]. Equol's SERMlike binding to ER-β within the prostate has positive implications in decreasing proliferation, inflammation and carcinogenesis [4,25] and down regulating ER-α which has a negative impact on prostate health [4].…”
Section: Discussionmentioning
confidence: 74%
“…Previous laboratories, including ours, have shown that isoflavones binding to ER-β in the prostate can down regulate the AR and thus decrease negative androgen hormone actions [28]. Moreover, this may explain how isoflavonoid molecules accumulate in prostate tissue and prostatic fluid after oral supplementation [29,30]. Equol's SERMlike binding to ER-β within the prostate has positive implications in decreasing proliferation, inflammation and carcinogenesis [4,25] and down regulating ER-α which has a negative impact on prostate health [4].…”
Section: Discussionmentioning
confidence: 74%
“…It has been suggested that chronic exposure to daidzein may increase the equol-producing capacity of the gut microbiota of mammals (Hedlund et al, 2005). Certain gastrointestinal bacteria are known to be stimulated by exposure to isofl avones (De Boever et al, 2000;Clavel et al, 2005), such that prolonged intake has been associated with altered isofl avone metabolism or absorption, or both, compared with single bolus doses (Lu and Anderson, 1998;Hedlund et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that soy may also affect other sex hormones, such as DHT, estrone and estradiol (Habito et al, 2000;Nagata et al, 2000;Dillingham et al, 2005). Moreover, isoflavones may protect against prostate cancer through non-hormonal mechanisms (Wang et al, 2003;Hedlund et al, 2005). For example, in vitro effects against insulin-like growth factor-1 and subsequent prostate cancer cell growth have been observed (Wang et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in vitro effects against insulin-like growth factor-1 and subsequent prostate cancer cell growth have been observed (Wang et al, 2003). As soy isoflavones have been detected in much higher concentrations in prostatic fluid than in the serum, they may also act locally (Hedlund et al, 2005). The small (14%) decline in mean serum PSA level on the high soy diet is consistent with an intervention using a soy protein supplement among prostate cancer patients that showed nonsignificant declines in serum PSA and free testosterone in the soy isoflavone supplemented group (Kumar et al, 2004).…”
Section: Discussionmentioning
confidence: 99%